Pathways to sustain atolls under rising sea levels through land claim and island raising. (16th February 2023) - Brown, Sally; Nicholls, Robert J; Bloodworth, Alan; Bragg, Oliver; Clauss, Audrey; Field, Stuart; Gibbons, Laura; Pladaitė, Milda; Szuplewski, Malcolm; Watling, James; Shareef, Ali; Khaleel, Zammath
Abstract: Low-lying atoll nations (e.g. the Maldives, Kiribati, Tuvalu, Marshall Islands) are highly vulnerable to climate change, especially sea-level rise (SLR). Stringent climate change mitigation will slow but not stop SLR, which will continue for centuries, mandating additional long-term adaptation. At the same time, urbanisation is concentrating population in a few centres, especially around capital islands which creates additional pressure as most atoll nations are 'land-poor'. This paper demonstrates how structural adaptation using land claim and island raising can be utilised within an adaptation pathway approach to sustain enough islands and land area above rising sea levels to satisfy societal and economic needs over multiple centuries. This approach is illustrated using the Maldives, especially around the capital and its environs (Greater Malé). Raising, expanding and connecting 'urban' islands can provide multiple benefits. Significant developments have already occurred in Greater Malé and further developments there and for other urban centres in the Maldives are expected. Migration to urban centres, especially Malé, is widespread and this adaptation approach assumes this trend continues, implying many other islands are depopulated or abandoned. Tourism is core to the Maldives economy and tourist islands require a different ambience to urban islands. They could be sustained with sympathetic soft engineering reinforcing the natural processes that produce atolls. While land advance and island raising provides a technical solution for SLR, any application must also address the additional policy, human, physical, engineering and economic/financial challenges that are raised. Nonetheless, by aligning adaptation through land advance/raising with existing development trends, atoll nations have the potential to persist and prosper for many centuries even as sea levels inevitably rise. This provides a realistic alternative to widespread assumptions about forced migration and ultimate national abandonment. The lessons here may find wider application to other small island settings and even mainland coasts.